Strategi Kepolisian Dalam Menanggulangi Penyalahgunaan Ciu Di Kalangan Anak SMA (Studi Kasus Polresta Surakarta) - Priyatmojo, Anggi Widhagdo, Dr. Natangsa Surbakti, S.H., M.Hum, Bambang Sukoco, SH.,M.H (2016)
This study aims to determine the things that encourages high school kids that consume ciu, to know the police efforts in tackling abuse ciu and form of sanctions given to high school students in Surakarta in the abuse ciu. This research method using juridical empirical approach is descriptive, the type of data in the form of primary data, secondary data such as interviews and primary legal materials, secondary and tertiary. Data were collected by interview and literature study, then the data were analyzed by qualitative analysis. The results showed the drivers of high school kids consume ciu due to environmental factors namely the family, community, and friends around. Police efforts in tackling abuse ciu by knowing the cause and then determined how to deal with it, namely the preventive, curative and development efforts. The sanctions given to high school students in Surakarta in the abuse Ciu namely by providing guidance to adolescents who do mischief done at home, school and in the community.